Institutional trading and asset pricing - Frijns, Bart; Huynh, Thanh D.; Tourani-Rad, Alireza; Westerholm, P. Joakim (Journal of Banking & Finance, 2018)
This paper examines whether the trading activity of different investor types, institutional versus retail, can affect the relation between beta and average returns. We find that the beta-return relation is strong and positive on days with high institutional trading activity, and negative and significant on low institutional trading days. Our findings are robust and not driven by recently documented effects such as macroeconomic news and leverage constraints, among others. The evidence is consistent with the hypothesis that the preferences and characteristics of various investor types, which are revealed through their trading activity, cause the slope of the Security Market Line to change.